Color Representation in Promotional Design on Indonesian E-commerce Website Interface - Lisa Odillia (International Journal of Seocology, 2022)
E-commerce is an effective channel for buying and selling goods and services via the internet. E-commerce can generally be accessed via smartphones and websites. As a visual product, the use of unaesthetic colors will affect the visual appearance of a website. In addition, the design features displayed must also be in accordance with the company's identity. Promotional banners are one of the features that are always updated (updated) in visual appearance, which of course must also be adjusted to the company's identity. Therefore, promotional media in the form of banners is used as an object of analysis to find out whether the colors in the promotional banner design represent the company's identity. This analysis in its elaboration uses the theory of color psychology which is then related to the company profile. The results of the analysis show that there is a match between the color of the banner design and the company profile.